Is there auditory impairment in Parkinson's disease? - Lopes,Marcia da Silva (2018)
ABSTRACT Objective: to describe the audiological profile of a group of patients with Parkinson's disease and to investigate the association between hearing loss and the disease. Methods: 50 individuals with and 46 without Parkinson's disease underwent Pure Tone Audiometry, Otoacoustic Emissions by Distortion Product, and auditory processing tests. The results of the patients were compared to those obtained in individuals without the disease, according to clinical and biological variables. Results: in individuals with Parkinson's disease, 82% presented hearing loss, 53.5% alterations in Otoacoustic Emissions by Distortion Product, 78%, alterations in temporal processing, and 12%, changes in binaural integration. Individuals with the disease had a greater impairment in the recognition of duration patterns when compared to those without the disease, with a worse performance in men and in individuals aged between 42 and 65 years old and Hoehn and Yahr I and II stages. Conclusions: the profile found corresponds to descending sensorineural hearing loss and alteration in otoacoustic emissions, temporal ordering and noise gaps detection.Only losses in temporal order are associated with the disease, especially in men, individuals under the age of 65 and in the initial stage.